2013
DOI: 10.7785/tcrt.2012.500350
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Cytotoxic T-Lymphocyte Antigen-4 −318C/T Polymorphism and Cancer Risk: A Meta-Analysis of Case-Control Studies

Abstract: results. We performed a meta-analysis to examine the association between CTLA-4 -318C/T polymorphisms and cancer susceptibility. Eligible studies were identified by searching several databases for relevant reports published up to September 30, 2012. Sixteen eligible studies with a total of 6190 patients and 6560 controls were included to summarize the association between CTLA-4 -318C/T polymorphisms and the risk of cancer. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies on the biological effects of miR-32 have mainly concentrated on tumors, viral replication and androgen regulation, which demonstrated that upon miR-32 overexpression, growth of the androgen-dependent prostate cancer cell line LNCaP was promoted. miR-32 has also been found to reduce apoptosis by directly regulating the expression of the BTG2 gene (55). Upregulation of miR-32 has been reported to inhibit the expression of apoptosis-inducing protein phosphoinositide-3-kinase interacting protein 1 and regulate the Ser/Thr protein kinase mitogen-activated protein kinase kinase, thus serving an important role in a variety of different signal transduction pathways (56).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the biological effects of miR-32 have mainly concentrated on tumors, viral replication and androgen regulation, which demonstrated that upon miR-32 overexpression, growth of the androgen-dependent prostate cancer cell line LNCaP was promoted. miR-32 has also been found to reduce apoptosis by directly regulating the expression of the BTG2 gene (55). Upregulation of miR-32 has been reported to inhibit the expression of apoptosis-inducing protein phosphoinositide-3-kinase interacting protein 1 and regulate the Ser/Thr protein kinase mitogen-activated protein kinase kinase, thus serving an important role in a variety of different signal transduction pathways (56).…”
Section: Discussionmentioning
confidence: 99%